Effect of geometrical parameters on Friction Stir Welding of AA 5083-H111 T-joints - Jesus, J. S. (2016)
The aim of this research is to study the effect of three different tool geometries and two joint geometries on quality of AA 5083-H111 T-welds done using the friction stir welding process (FSW). All the tools have concave shoulder with different pin geometries: tapered and threaded, quadrangular pyramidal and progressive pin, part threaded cylindrical and part pyramidal. T-lap and T-butt joints configurations have been studied. Tunnel and kissing-bond type defects have been found in joints produced with a pyramidal pin tool, while welds produced with the tapered pin tool only show presence of oxide lines. Sound welds were produced with the progressive tool. No significant change in hardness has been observed in all combinations of tool and joint geometry. The tensile strength efficiency in joints welded with the progressive pin tool has been found to be 100%. The fatigue results(R=0) show a higher fatigue strength of FSW T-joints than T-joints welded by conventional process as Metal Inert Gas (MIG).